2013
DOI: 10.1152/jn.00128.2013
|View full text |Cite
|
Sign up to set email alerts
|

Feedback that confirms reward expectation triggers auditory cortex activity

Abstract: Associative learning studies have shown that the anticipation of reward and punishment shapes the representation of sensory stimuli, which is further modulated by dopamine. Less is known about whether and how reward delivery activates sensory cortices and the role of dopamine at that time point of learning. We used an appetitive instrumental learning task in which participants had to learn that a specific class of frequency-modulated tones predicted a monetary reward following fast and correct responses in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…Notably, the sensory basis network also learns based on the back-propagated reward prediction error. This is in line with experimental findings indicating that early auditory cortical areas are activated in response to dopaminergic reward signals (Puschmann et al, 2012) and show learning-dependent plastic changes (Weis et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, the sensory basis network also learns based on the back-propagated reward prediction error. This is in line with experimental findings indicating that early auditory cortical areas are activated in response to dopaminergic reward signals (Puschmann et al, 2012) and show learning-dependent plastic changes (Weis et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
“…We would expect representations of stimuli that belong to the same task category, i.e., that differ only along dimensions that are non-discriminative with respect to the task, to show much higher correlations among each other than with representations of stimuli that belong to a different task category. While this hypothesis still requires further experimental work, there are indications that task-dependent representations exist in sensory cortices (Ohl et al, 2001; Weis et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with the presentation of the line graph, a happy or sad sound played if the difficulty level moved up or down, respectively. This feature was included to increase the interactivity of the system and increase subjects engagement with the task, as previous research has shown that engaging the auditory system through reward processing can increase task performance (Weis et al, 2013a,b). …”
Section: Methodsmentioning
confidence: 99%
“…Sensory plasticity is however only observed if a cognitive association is formed between the reinforcer and the sensory stimulus (Blake et al, 2006; Puschmann et al, 2013). Recently, several studies in humans have shown that even rewarding outcomes which follow the sensory stimuli activate respective sensory cortices in the absence of the respective sensory input (Pleger et al, 2008, 2009; Weil et al, 2010; Fitzgerald et al, 2013; Weis et al, 2013). In the studies by Pleger et al (2008, 2009) participants had to discriminate somatosensory stimuli applied to an index finger and received a visually presented monetary reward for correct performance.…”
Section: Introductionmentioning
confidence: 99%